Clinical Application of Ischemic Preconditioning in the Elderly - Pasquale Abete; Francesco Cacciatore; Gianluca Testa; David Della-Morte; Gianluigi Galizia; Nicola Ferrara; Franco Rengo (SAGE Publishing, 2010)
A mild stress such as brief ischemic episodes may protect the heart from a successive and more prolonged myocardial ischemia (ischemic preconditioning). This phenomenon is considered a typical "hormetic mechanism" by which the heart is immunized from pathological insults such as myocardial ischemia. This mechanism is reduced with aging and it may be restored and/or preserved by drugs such as adenosine or nicorandil, a mitochondrial K ATP channels, and lifestyle interventions such as physical activity and/or hypocaloric diet. Moreover, since the mechanisms involved in cardiac ischemic preconditioning have been established basic and clinical investigators are encouraged to test several drug in well-controlled animal and human studies in order to prevent and/or restore the age-related reduction of ischemic preconditioning.